An interesting case of cardiac sarcoidosis presenting as recurrent syncopal attacks - Thanawala, Akshat Rahul; Patel, Alpa Nimesh; Solanki, Harsh Baldev; Jamnani, Raghav Santosh; Patel, Naman Gautam; Trasadiya, Jaimin Prabhu Bhai (Indian Journal of Case Reports, 2025)
The cardiac cause of syncope has traditionally been associated with conduction or valvular abnormalities. We present a rare case of isolated cardiac sarcoidosis in a 45-year-old Indian male, presenting with only syncope as the primary complaint. It remains a diagnosis of exclusion in such clinical presentations. Fluorodeoxyglucose positron emission tomography and cardiac magnetic resonance imaging (MRI) are newer modalities relied on for diagnosis. The patient was ultimately diagnosed based on cardiac MRI findings and correlating abdominal lymph-node biopsy. He was treated with oral steroids, and methotrexate was introduced gradually.